Profile of Mathematical Critical Thinking Abilities of Vocational School Students on Quadratificial Equations Based on Ennis Indicators - Dwi Putri Azisa; Syahrir Syahrir; Masjudin Masjudin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Mathematical critical thinking ability is an important skill that students must have in learning mathematics. However, the lack of clear data regarding this ability at SMKN 7 Mataram prompted this study. This study aims to analyze the mathematical critical thinking ability of grade X students of SMKN 7 Mataram on quadratic equations. The study used a qualitative approach with a descriptive type. The research subjects were 460 students from 13 classes. Data were collected through tests, interviews, and documentation, then analyzed using the Miles and Huberman model. The results showed that students' mathematical critical thinking ability was in the medium category, with 102 students (22.22%) in the high category, 230 students (50.00%) in the medium category, and 128 students (27.78%) in the low category. Students in the high category were able to fulfill almost all critical thinking indicators, while students in the medium and low categories still experienced difficulties in providing arguments and evaluating the results of problem solving. The results of this study are expected to be a basis for improving students' mathematical critical thinking ability through more effective learning.